2013
DOI: 10.1007/s10072-013-1359-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric screening for migraine patients

Abstract: Psychiatric disorders in migraine patients have a higher prevalence than general population. The presence of psychiatric comorbidities may influence the complexity of the migraine pictures and be related to medication overuse. Severely impaired chronic migraineurs presenting with medication overuse are a challenge for headache clinics. Psychiatric comorbities, such as dependency-like behaviors, anxiety and mood symptoms, might account for headacherelated disability and recurrent relapses into medication overus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…To the best of our knowledge, only a few studies (28,34,35) have evaluated changes in terms of depression and anxiety after a detoxification program according to the outcome. However, two main differences can be observed between those studies and the present one.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only a few studies (28,34,35) have evaluated changes in terms of depression and anxiety after a detoxification program according to the outcome. However, two main differences can be observed between those studies and the present one.…”
Section: Discussionmentioning
confidence: 99%
“…patientsNo. medication overuse headacheAnalgesicsErgotsOpioidsTriptansAltieri et al 2009 [11]ItalyICHD-2 [7]Clinic2711NRNR4Ayzenberg et al 2008 [12]GermanyICHD-2 [7]Clinic2914NRNR15Biagianti et al 2012 [13]ItalyICHD-2 Revised [8]Clinic5226NRNR20Boe et al 2007 [14]NorwayICHD-2 Appendix [7]Clinic100201NR23Coppola et al 2010 [15]ItalyICHD-2 Appendix [7]Clinic2910NRNR9Cupini et al 2009 [16]ItalyICHD-2 Appendix [7]Clinic33NR1NR4Di Lorenzo et al 2009 [17]ItalyICHD-2 [7]Clinic10718NRNR29Donnet et al 2009 [18]FranceICHD-2 [7]Population320157252964Dousset et al 2013 [19]FranceICHD-2 Appendix [7]Clinic428109Galli et al 2011 [20]ItalyICHD-2Appendix [7]Clinic82212322Gambini et al 2013 [21]ItalyICHD-2 Revised [8]Clinic6333NRNR21…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary findings from this sample regarding clinical improvements associated with detoxification were recently published [21]. For the purpose of this retrospective analysis, we focused on the following battery of assessments.…”
Section: Methodsmentioning
confidence: 99%
“…We previously conducted an observational single-arm study on subjects with CMwMO referred to our headache center for a detoxification program. When looking at migraine characteristics and related disability prior-to, and then 1-year-after detoxification, we found that detoxification was associated with significant improvements in the group taken as a whole [21]. In this retrospective analysis, we decided to study comparatively those who did not fall into medication overuse throughout the 12 months following the detoxification and those who relapsed into CMwMO.…”
Section: Introductionmentioning
confidence: 99%